Early, specialist vocational rehabilitation to facilitate return to work after traumatic brain injury: the FRESH feasibility RCT - Radford, Kathryn A.; Sutton, Chris; Sach, Tracey; Holmes, Jain; Watkins, Caroline L.; Forshaw, Denise; Jones, Trevor; Hoffman, Karen; O’Connor, Rory C.; Tyerman, Ruth; Merchán-Baeza, Jose Antonio; Morris, Richard; et al. (NIHR Journals Library, 2018)
Background